CD4 Counts and Viral Loads of Newly Diagnosed HIV-Infected Individuals: Implications for Treatment as Prevention - Govender, Sarishen (Public Library of Science, 2014)
OBJECTIVE: To report the viral load and CD4 count in HIV-infected, antiretroviral naïve, first -time HIV-testers, not immediately eligible for treatment initiation by current South Africa treatment guidelines. DESIGN: This was a cross-sectional study in a high-volume, free-of-charge HIV testing centre in Soweto, South Africa. METHODS: We enrolled first time HIV testers and collected demographic and risk-behaviour data and measured CD4 count and viral load. RESULTS: Between March and October 2011, a total of 4793 adults attended VCT and 1062 (22%) tested positive. Of the 1062, 799 (75%) were ART naïve and 348/799 (44%) were first-time HIV testers. Of this group of 348, 225 (65%) were female. Overall their median age, CD4 count and viral load was 34 years (IQR: 28-41), 364 (IQR: 238-542) cells/mm(3) and 13,000 (IQR: 2050-98171) copies/ml, respectively. Female first time HIV testers had higher CD4 counts (419 IQR: 262-582 vs. 303 IQR: 199-418 cells/mm(3)) and lower viral loads (9,100 vs. 34,000 copies/ml) compared to males. Of 183 participants with CD4 count >350 cells/mm(3), 62 (34%) had viral loads > 10,000 copies/ml. CONCLUSIONS: A large proportion of HIV infected adults not qualifying for immediate ART at the CD4 count threshold of 350 cells/mm(3) have high viral loads. HIV-infected men at their first HIV diagnosis are more likely to have lower CD4 counts and higher viral loads than women.